Analisis Efektivitas Sistem Informasi Manajemen dalam Meningkatkan Kinerja Perusahaan - Hardianti, Hardianti; Bakti, Andi Amri; Bohari, Bohari; Swandani, Swandani (STMIK Amika Soppeng, 2025)
The phenomenon in this study looks at the Performance of PT RACHITA. Without an effective Management Information System, the company may not be able to monitor and analyze performance accurately, so that it cannot improve company performance optimally. The purpose of this study is to analyze the effectiveness of the Management Information System in improving company performance. This type of experimental research uses a pre-test and post-test design, namely measuring company performance before and after the implementation of the Management Information System. The data sources used in this study are primary and secondary data. Data collection techniques used are observation, interviews, and tests. The data analysis method used is Descriptive Statistical Analysis, Wilcoxon Test, Homogeneity Test. The results of the study The Implementation of Management Information Systems (MIS) has a positive impact on company performance. The results of the data analysis show that the implementation of MIS can improve company performance by providing accurate and timely information, increasing the efficiency and effectiveness of business processes, and reducing employee workload. The results of the Wilcoxon test show that there is a significant difference between company performance before and after the implementation of MIS.